2018
DOI: 10.1007/s00134-018-5448-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative versus standard pupillary light reflex for early prognostication in comatose cardiac arrest patients: an international prospective multicenter double-blinded study

Abstract: PurposeTo assess the ability of quantitative pupillometry [using the Neurological Pupil index (NPi)] to predict an unfavorable neurological outcome after cardiac arrest (CA).MethodsWe performed a prospective international multicenter study (10 centers) in adult comatose CA patients. Quantitative NPi and standard manual pupillary light reflex (sPLR)—blinded to clinicians and outcome assessors—were recorded in parallel from day 1 to 3 after CA. Primary study endpoint was to compare the value of NPi versus sPLR t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
176
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(196 citation statements)
references
References 35 publications
3
176
0
5
Order By: Relevance
“…Recently, NPi was reported to show a high specificity in predicting poor neurological outcome in a large multicenter study [12]. Although the algorithm of NPi calculation is not disclosed, it is composed of several pupillary parameters showing high correlation with PLR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, NPi was reported to show a high specificity in predicting poor neurological outcome in a large multicenter study [12]. Although the algorithm of NPi calculation is not disclosed, it is composed of several pupillary parameters showing high correlation with PLR.…”
Section: Discussionmentioning
confidence: 99%
“…First, a weak point of this study was the lack of data on in-hospital treatment, including whether extracorporeal CPR, percutaneous coronary intervention, and therapeutic hypothermia management were performed, which are relevant clinical factors that could affect patient outcomes [25][26][27]. Second, prognostic factors after hospital arrival, such as lactate clearance, pupillary light reflex, or pattern of amplitude-integrated electroencephalography, were unavailable [28][29][30]. Third, we could not assess detailed information on the difference in medical staff or organization of resuscitation teams at each hospital among the three groups, considering whether the meeting had been held in the Tokyo metropolitan area or other areas.…”
Section: Discussionmentioning
confidence: 99%
“…One multicenter study recently compared quantitative automated pupillary light reflex and neurological pupillary index (NPi; using the NeurOptics NPi-200, NeurOptics, Laguna Hills, CA) to manual pupillary light reflex in comatose cardiac arrest patients and found that an NPi ≤2, performed between days 1 and 3 following cardiac arrest, was 100% specific for an unfavorable 3-month neurological outcome when compared to manual pupillary light reflex [7].…”
Section: Prognosis Following Cardiac Arrestmentioning
confidence: 99%